A Systematic Literature Review of Competitive Strategies for Indonesian Tourism Villages - Ardiansyah, Imam; Muntasib, E.K.S Harini; Soekmadi, Rinekso; Rachmawati, Eva (E-Journal of Tourism, 2025)
Tourist villages have increasingly become a focus of academic and practical interest. Despite numerous studies, comprehensive analyses to uncover key contexts and topics remain limited. Indonesia, which leads in publications on tourist villages, offers a unique opportunity to explore strategies for enhancing its competitiveness. This study aims to review, synthesize, and advance the competitiveness of Indonesian tourist villages by examining theoretical frameworks, sustainability challenges, and strategic approaches. The combination of the approaches describes the novelty of this study. A systematic literature review analyzed 21 Scopus-indexed articles from 2023–2024, selected based on open access and journal publication criteria. The review highlights that most research focuses on Java-based villages, utilizing theories like social capital, sustainable tourism, and community-based tourism. Results show that the key success factors for tourist villages include collaboration and cultural preservation, while challenges span economic, social, cultural, and environmental dimensions. The study emphasizes the potential of analytical tools like VRIO and PESTLE to help identify competitive advantages and address vulnerabilities. These frameworks provide actionable insights for improving resilience and ensuring the sustainable appeal of tourist villages in Indonesia. By addressing these critical aspects, the study offers valuable guidance for enhancing the long-term viability and success of tourist villages as a cornerstone of Indonesia’s tourism industry.